Asuhan Kebidanan Pada Bayi Baru Lahir Di PMB Nelly Suryani Wilayah Kerja Puskesmas Kuok - Enjelika, Enjelika; Apriyanti, Fitri; Miftahurrahmi, Miftahurrahmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Newborn normally or commonly called neonates is a baby born with a gestational age of more than 37 weeks with a weight of 2500-4000 grams. Providing midwifery care by using the midwifery management approach to newborns. A in PBM Nelly Suryani Kuok Village, Kuok District in 2022. The design of this research is descriptive, which is to describe or describe the description of the level of knowledge in newborn mothers in PMB Nelly, Kuok Village, Kuok District. This study is the study and collection of basic data which is the initial stage of midwifery management is carried out using SOAP with Varney's mindset, namely subjective data assessment, objective data assessment, analysis and management in accordance with the problems complained of by. Ny. A is a normal newborn baby. Based on the monitoring given for 8 days, the care given to Ny. A went smoothly and there was a decrease in pain felt by Ny. A During the provision of care and care provided has been running comprehensively.